Enhancing Learning Interaction through Inter-Forum Group Discussion in Online Learning: A Case Study on Online Teaching of Research in English Language Teaching Course - Antoro, Sunu Dwi; Sudilah, Sudilah (Ahmad Dahlan Journal of English Studies, 2016)
This research aimed to develop a model of Inter-Group Discussion Forum (IGDF) application Â Â as media to increase studentsâ interaction and participation in the discussion forum during the online learning. Data were collected through the process of the implementation of discussion forum using IGDF application during the online learning of Research in English Language Teaching (ELT) courses during the teaching period of 2014.2. Data of the students participation were collected through online observation, and data about the studentsâ perception of the IGDF model were collected by providing an online close and open ended questionnaires and analyzed by calculating the percentage. The results of this study indicated that the application of IGDF is applicable in online learning. The amount of participation and the quality of the interaction from the discussion through IGDF has not shown significant improvement. The main obstacle came from the technical problems associated with passwords and the ability to follow the discussion in a discussion forum between groups. However, the variety types of posting has increased. Each group is able to post presentations, questions, responses, and commands. Students perceptions toward the IGDF proved significant where there was 88.46% of them stated that the discussion forum with IGDF is very good discussion among the group and it can increase interaction among students in the online learning.